Hybrid energy storage system using bidirectional single-inductor multiple-port converter with model predictive control in DC microgrids - Wang, Benfei (2020)
This paper presents a bidirectional single-inductor multiple-port (BSIMP) converter for integrating hybrid energy storage system (HESS) into DC microgrids, where the HESS is the combination of different types of energy storages (ESs). A control method based on model predictive control (MPC) is proposed to regulate the BSIMP converter for the HESS. With the MPC-based method, the ESs are controlled following their characteristics. Simultaneously, the DC microgrid bus voltage can be maintained against the fluctuations of the load consumption and renewable generation. Compared to conventional bidirectional single-input single-output converters, the proposed BSIMP converter significantly reduces the component count, system size and cost to integrate the HESS into DC microgrid. To verify the performance of the proposed BSIMP converter with MPC-based method, a series of hardware-in-loop (HIL) experimental cases are studied. Moreover, the comparison with previous works is conducted. The HIL experimental and comparison results demonstrate the successful regulation of HESS using the BSIMP converter in DC microgrid.